Manajemen Proteksi Dan Keselamatan Radiasi Dalam Penggunaan Pesawat Sinar-X C-Arm Di Kamar Bedah Rumah Sakit Umum Haji Surabaya - Mas Winarto; Indasah Indasah (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Occupational Health and Safety efforts should be organized to realize optimal work productivity in all workplaces, especially places that are at risk of health hazards, are susceptible to disease or have employees of at least 10 people. Radiology services using C-Arm X-ray aircraft in the Surgical Room is very important because it is needed as a guding of surgery. This shows that the need to study further related to radiation protection and safety management in the use of C-ARM X-ray aircraft in the surgical room of Haji Surabaya General Hospital.Methods: Design observational research using qualitative descriptive methods. The study setting used the selection of informants through primary data and secondary data. The study used purposive sampling techniques. The research instrument uses observation sheets and interview guidelines. The trial was conducted at RSU Haji Surabaya held in March-June 2021. Data analysis techniques used in research are data reduction, data presentation and conclusion withdrawal.Results: The results of the study showed licensing requirements, the use of C-Arm X-Ray aircraft in the surgical room unit of RSU Haji Surabaya already has permission from the head of BAPETEN and meets radiation safety requirements in the use of X-ray aircraft. The use of C-Arm X-Ray aircraft in the surgical room unit of RSU Haji Surabaya already has a radiation safety responsibility consisting of permit holders and other parties related to the implementation of the use of X-ray aircraft.Conclusions: The potential danger of radiation in the use of X-rays is very large, the safety factor is important so as to minimize the risk of work in radiology installations and the impact of radiation on radiation workers. Five research variables consisting of licensing, management requirements, protection requirements, engineering requirements, and safety verification in this study have met the requirements.